Використання прибутку підприємства в умовах здійснення модернізації та оновлення виробництва - Следь, О.М. (Стратегія і механізми регулювання промислового розвитку, 2014)
Досліджено підходи до формування та використання чистого прибутку підприємств. Встановлено систему пропорцій поділу прибутку на частину, що капіталізується (кошти на виробничий розвиток, формування резервного фонду), і частину,що споживається (кошти на виплату дивідендів, матеріальне стимулювання персоналу і соціальний розвиток підприємства). Запропоновано метод визначення структури використання чистого прибутку підприємства, що забезпечує приріст коштів, які спрямовуються на розвиток виробництва. Исследованы подходы для формирования и использования чистой прибыли предприятий. Установлена система пропорций деления прибыли на часть, которая капитализируется (средства на производственное развитие, формирование резервного фонда), и часть, которая потребляется (средства на выплату дивидендов, материальное стимулирование персонала и социальное развитие предприятия). Предложен метод определения структуры использования чистой прибыли предприятия, обеспечивающий прирост средств, направляемых на развитие производства. The article studies the characteristics of using the profits of enterprises under conditions of need for production upgrading. Found that one of the best reasons for insufficient technical and technological renewal of production base is limited own funds of enterprises, while the absence of state innovation stimulation tool exists. Experience of the process of updating and remodeling at leading machine-building enterprises and economic justification of purposeful patterns of the net profits distribution indicate the need and possibility of establishing a rational structure of the net income, part of which is directed at the development of production and 50% of funds received. Research approaches to the formation and use of the enterprise profits revealed a system of proportions of profit division, that covers the capitalized part (funds for industrial development, the formation of the reserve fund), and part of that is consumed (funds for dividend payments, financial incentives for staff and social development of the company). A method of determining the structure of using net profit that provides growth funds allocated for the development of production is proposed.A need for upgrading the production makes it necessary to increase the portion of net income that is capitalized, that is, the proportion of funds allocated for the development of production. An important prerequisite for this is to provide a simultaneous increase in profits across other directions, or at least not decrease admission of the income that is consumed. In particular this applies to funds allocated for social development, reproduction and accumulation of intellectual capital as a major factor in technological development and improve production. It is also necessary to strengthen the financial incentives for workers who learn new techniques and technologies to improve the efficiency upgrading of production and prevent resistance from the staff. The net income used for investment upgrading purposes is advisable to distribute the production in view of the natural changes in the structure of fixed assets due to an accelerated rate of growth in the value of machinery and equipment compared to the cost of buildings and construction works through the use of appropriate correction factor for the proportion of active part of fixed assets.